“Eu sou o filho da Terra!”: educação ambiental crítica e o sujeito ecológico na relação entre escola e unidades de conservação. - Lobo, Lara Bittar (2025)
This master’s thesis investigates the challenges and possibilities of integrating Critical Environmental Education (CEE) into daily school routines, focusing on the articulation between the State School Prof. Arquimínio Marques da Silva (Sorocaba/SP) and the Ipanema National Forest (Flona Ipanema) (Iperó/SP). The study is based on the hypothesis that there is a gap in the implementation of critical environmental education principles in both formal school environments and Protected Areas (PAs), which calls for an investigation into whether mediation between these spaces can address such a deficiency. The primary objective was to analyze the effectiveness of educational practices in these institutions and propose actions to strengthen their integration through the lens of Socio-environmental Geography. Methodologically, the research is anchored in Freirean-based propositive research, utilizing focus groups with teachers and semi-structured interviews with environmental guides to diagnose the challenges presented. The theoretical framework is grounded in authors such as Loureiro, Tozoni-Reis, Porto-Gonçalves, Mendonça and Freire. The results reveal that, despite severe institutional barriers — such as curricular fragmentation, lack of time, and limited resources —, there is a genuine enthusiasm among educators to connect school content with practical experiences, as well as among environmental guides during guided trails. In response to these limitations, the research presents, in its final chapter, an Interdisciplinary Action Plan that materializes the "untested feasibility" (inédito viável), integrating skills from National Common Curricular Base (BNCC) with thematic axes linked to the Ipanema National Forest. It concludes that overcoming the neutrality of knowledge requires a praxis that transforms the Protected Area into a living laboratory of citizenship, reaffirming Environmental Education as an act of resistance and a structural principle for understanding the complexity of the contemporary world.